Sarana dan Prasarana Pendukung Kegiatan Majelis Taklim Muslimah Kaffah Kecamatan Percut Sei Tuan - Siti Khoirotun Nisa; Sri Dame Marulina Manik; Muhammad Hanafi; Ilham; Hendra Kurniawan (Medan Resource Center, 2025)
Majelis Taklim Muslimah Kaffah in Percut Sei Tuan District is a non-formal educational institution that plays an important role in enhancing religious understanding and spirituality among women. The success of Majelis Taklim activities is closely related to the availability of adequate facilities and infrastructure that support the learning process. This study aims to identify and analyze the supporting facilities and infrastructure of Majelis Taklim Muslimah Kaffah and their impact on the effectiveness of religious activities. This research employed a qualitative approach, with data collected through observation and in-depth interviews with the management and founders of the Majelis Taklim. The data were analyzed using descriptive qualitative analysis through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that facilities such as meeting spaces, learning media, and internet access, as well as infrastructure including road access, parking areas, and sanitation facilities, play a significant role in enhancing participants’ comfort, participation, and learning quality. However, the study also identified several challenges, including limited funding, inadequate facility maintenance, and limited human resources in managing facilities and infrastructure. Therefore, systematic and sustainable management of facilities and infrastructure is necessary to optimize the activities of Majelis Taklim Muslimah Kaffah.